Barriers to behavioral health service utilization among first-generation immigrant emerging adults. Issue 1 (2nd January 2020) - Bessaha, Melissa L.; Cornelius, Llewelylln; Unick, George Jay
ABSTRACT: Compared to other adult age groups, emerging adults experience more behavioral health problems yet use less supportive services. First-generation immigrant emerging adults may experience additional stressors including institutional barriers. Factors associated with behavioral health service use were explored among 6, 696 first-generation immigrant and U.S.-born emerging adults. Employed first-generation and Black U.S.-born emerging adults were less likely to use services compared to unemployed and White emerging adults, respectively. Having health insurance for U.S.-born emerging adults was associated with service use. Findings portray the need for more consideration of barriers to behavioral health treatment on healthcare policies and higher education programming to promote the successful transition to adulthood.